Rancang Bangun Pemantau Daerah Endemik Malaria Berbasis IoT Menggunakan Metode Profile Matching - Rama Sahtyawan; Landung Sudarmana (LPPM Universitas Merdeka Madiun, 2020)
Abstractâ€” Malaria is an endemic disease transmitted by Anopheles mosquitoes, which causes increased morbidity and mortality (morbidity and mortality), maternal and child health disorders, intelligence, labor force productivity, and detrimental to tourism. From these problems, a tool was developed to monitor endemic malaria areas in real-time by using temperature and humidity data for an area. Then analyzed using the profile matching method to calculate the weight/score gap in temperature and humidity conditions using interpolation, the data will be sent by the DHT 11 sensor found on NodeMcu. The application used to find out in real-time using the Blynk application as an internet of things board with a Wifi connection for the next step NodeMcu requires coding using the Arduino IDE program, for testing the location system used consists of 5 locations namely: L1 = Jl.Magelang, L2 = Jl.Maguwoharjo, L3 = Jl.Babarsari, L4 = Jl.Wates km9, L5 = Jl.Ali times km 8. Obtained temperature and humidity data (L1 = 36.30), (L2 = 18.32), (L3 = 23.45), (L4 = 38.33), (L5 = 35.53), then the gap weight calculation using the interpolation method obtained temperature and humidity data (L1 = 3,800; 3,974), (L2 = 4,600; 4,179), (L3 = 5,000; 5,000), (L4 = 3,400; 4,282), (L5 = 4,000; 5.00), the results obtained from rank 5 locations are malaria-endemic areas, rank 1 = L3-Babarsari, rank 2 = L5-Jl.Kaliurang km 8, rank 3 = L2-Jl.Maguwoharjo, rank 4 = L1-Jl.Magelang, rank 5 = L4-Jl.Wates. from the ranking data, the location must be prioritized L3-Babarsari.Â Keywordsâ€”: Malaria; DHT 11, NodeMCU; Profile Matching; Blynk.